Pengaruh Kombinasi Kerapatan Kanopi Pohon terhadap Kenyamanan Termal di Lapangan Puputan Margarana, Denpasar - Bagas Utomo Putra; Anak Agung Keswari Krisnandika; I Made Agus Dharmadiatmika (http://arl.faperta.ipb.ac.id/, 2022)
Puputan Margarana as a city park is used as a public space that can accommodate outdoor activities for its users. Comfort is an important factor consider for users to conduct activity inside. User comfort level can be measured using the thermal humidity index formula based on the temperature and humidity variables. The temperature and humidity can be influenced by the presence of vegetation, especially trees. Differences in tree species composition will cause differences in the canopy density formed. This study aims to identify the effect of the combined tree canopy density on thermal comfort. This research method begins with determining the sample point based on the combination of canopy density to areas that are not shaded by the canopy. Then, the canopy was photographed at the sample point for analysis using Hemiview 2.1 software to obtain the leaf area index (LAI) value. Furthermore, independent samples T test, assessment of thermal comfort, correlation analysis and linear regression between variables. The results of the analysis show that there is a strong correlation between LAI with temperature, humidity, and THI. There were significant differences between THI at sample points 1, 2, 4, and 5 with LAI 1.68-4.53 against THI without canopy shade. Meanwhile, THI at sample points 3 and 6 with LAI 0.96-1.36 was not significantly different from THI without canopy shade. This shows that the combination of tree canopy density in this study has an effect on thermal comfort. This shows that canopy density can be one of the considerations in selecting trees for landscape design for climate engineering purposes.